2021
DOI: 10.1182/blood.2020005407
|View full text |Cite
|
Sign up to set email alerts
|

Specialized regulatory T cells control venous blood clot resolution through SPARC

Abstract: The cells and mechanisms involved in blood clot resorption are only partially known. We show that regulatory T (Treg) cells accumulate in venous blood clots and regulate thrombolysis by controlling the recruitment, differentiation and matrix metalloproteinase (MMP) activity of monocytes. We describe a clot Treg population that forms the matricellular acid- and cysteine-rich protein (SPARC), show that SPARC enhances monocyte MMP activity and that SPARC+ Treg are crucial for blood clot resorption. By comparing d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 59 publications
0
26
0
2
Order By: Relevance
“…We found an association between CSF lymphocyte count and percent IVH clearance, which may be due to crosstalk between lymphocytes and the coagulation system. In addition to crosstalk with platelets [ 34 ], regulatory T cells producing SPARC (secreted protein acidic and rich in cysteine) are crucial for blood clot resorption [ 35 ] and may contribute to reduction of hemorrhage volume.…”
Section: Discussionmentioning
confidence: 99%
“…We found an association between CSF lymphocyte count and percent IVH clearance, which may be due to crosstalk between lymphocytes and the coagulation system. In addition to crosstalk with platelets [ 34 ], regulatory T cells producing SPARC (secreted protein acidic and rich in cysteine) are crucial for blood clot resorption [ 35 ] and may contribute to reduction of hemorrhage volume.…”
Section: Discussionmentioning
confidence: 99%
“…In this issue of Blood, Khan et al 1 reported that high-dose chemotherapy and autologous hematopoietic cell transplantation (auto-HCT) are associated with decreased fecal microbiota diversity and that patients with a greater degree of microbiome damage (below-median fecal intestinal diversity) at neutrophil engraftment had worse progression-free survival than those with less microbiome damage.…”
Section: Let's Reconstitute Microbiota Diversitymentioning
confidence: 99%
“…Here, the authors have characterized these thrombus Tregs and elucidate their role in thrombus resolution. 1 To induce a thrombus, the authors used a mouse model of partial flow reduction in the inferior vena cava. By isolating immune cells at different time points after the partial occlusion, they showed that Tregs accumulate in the thrombus over time.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Shahneh et al, 20 in a series of sophisticated experiments, elaborate on another previously understudied adaptive immune cell in venous thrombus resolution: the regulatory T cell (Treg). Tregs, identified as CD4+, CD25+ cells with selective expression of Foxp3, function as immunomodulators, essential for preventing exuberant inflammation.…”
mentioning
confidence: 99%